Analysis And Design Of Standard Operating Procedures In Pt. Xyz Server Room Using Tia-942 And Iso/iec 27002 - Astrid Natania Mentang; Avon Budiono; Ahmad Almaarif (eProceedings of Engineering, 2020)
Abstract As a private company engaged in data center services, it should have business process procedures that can facilitate the implementation of tasks and work in the company. However, in the management of existing regulations in the company to support this business process, there are problems that can hinder the work of employees. The cause of this problem is the absence of SOPs that regulate the work of existing employees as a result of which employees become confused about carrying out their activities and experience problems, namely inefficient time which can prevent employees from executing an on-going activity. Based on these problems, an SOP design is needed to simplify and help make work more efficient, as well as an SOP design that must meet the specified standards, namely TIA-942 and ISO 27002, both of these standards function to optimize business processes and activities in the company, namely focusing on data security as well as the company's data centre infrastructure. Keywords: Data centre, Standard Operating Procedure, TIA-942, ISO 27002 Abstrak Sebagai perusahaan swasta yang bergerak di bidang jasa data center harus memiliki prosedur proses bisnis yang dapat memudahkan pelaksanaan tugas dan pekerjaan di perusahaan tersebut. Namun dalam pengelolaan regulasi yang ada di perusahaan untuk mendukung proses bisnis ini, terdapat permasalahan yang dapat menghambat kerja karyawan. Penyebab dari permasalahan tersebut adalah tidak adanya SOP yang mengatur pekerjaan pegawai yang ada akibatnya pegawai menjadi bingung dalam menjalankan aktivitasnya dan mengalami permasalahan yaitu waktu yang tidak efisien yang dapat menghambat pegawai untuk melaksanakan suatu kegiatan yang sedang berlangsung. Berdasarkan permasalahan tersebut maka diperlukan suatu desain SOP untuk mempermudah dan membantu agar pekerjaan menjadi lebih efisien, serta desain SOP yang harus memenuhi standar yang ditentukan yaitu TIA-942 dan ISO 27002, kedua standar tersebut berfungsi untuk mengoptimalkan proses bisnis dan kegiatan di perusahaan, yaitu fokus pada keamanan data serta infrastruktur pusat data perusahaan. Kata kunci: Data centre, Standard Operating Procedure, TIA-942, ISO 27002